Si le das una galletita a un raton - Numeroff, Laura Joffe; Bond, Felicia (New York : Scholastic, 1996)
Relating the cycle of requests a mouse is likely to make after you give him a cookie takes the reader through a young child's day.
Between the Lions recommended books.
Originally published: New York : Harper Arco Iris, 1995.
Keywords: Mice -- Fiction; Spanish language materials